Modified citrus pectin inhibited bladder tumor growth through downregulation of galectin-3 - Fang Tian; Liu Dan-dan; Ning He-ming; Liu Dan; Sun Jing-ya; Huang Xiao-jing; Dong Yu; Geng Mei-yu; Yun Shi-feng; Yan Jun; Huang Rui-min (Acta Pharmacologica Sinica; Vol 39, No 12 (December 2018): Acta Pharmacologica Sinica, 2018)
Modiﬁed citrus pectin (MCP) is a carbohydrate enriched complex, which has been implicated in cancer treatment and prevention. However, the effects of MCP on urinary bladder cancer (UBC) are unknown. In this study, MCP was ﬁrst tested in T24 and J82 human UBC cells and showed the inhibition of cell viability by the sulforhodamine B (SRB) assay. The MCP-treated UBC cells exhibited G2/M phase arrest with the decrease of Cyclin B1 and phosphorylated Cdc2. Caspase-3 was also activated, leading to the cleavage of Caspase-3 and PARP. We further explored the possible molecular mechanisms upon MCP treatment in UBC cells. Reduction of galectin-3 was observed and followed with the inactivation of Akt signaling pathway. Of note, galectin-3 knockdown by RNA interference recapitulated the MCP-mediated anti-proliferation, cell cycle arrest and apoptosis. Moreover, oral administration of MCP to the T24 xenograft-bearing nude mice inhibited the tumor growth signiﬁcantly (P < 0.05). Quantiﬁcation analysis of immunohistochemistry staining for Ki67 and cleaved Caspase-3 conﬁrmed the decrease of proliferation index (P < 0.05) and the increase of apoptosis index (P < 0.01) in 700 mg/kg MCP-fed UBC xenografts. Using the information from TCGA database, we revealed that the overexpression of galectin-3 was associated with high tumor grade with lymph node metastasis, poor overall survival in UBC patients. Considering the remarkable inhibitory effects of MCP on UBC cell proliferation and survival in vitro and in vivo mainly through galectin-3, which is upregulated in UBCs, MCP may become an attractive agent, as a natural dietary ﬁber, for prevention and therapy of UBCs.